Implementasi Peraturan Walikota Surabaya Nomor 58 Tahun 2019, Tata Cara Pengumpulan, Pengolahan, Pemanfaatan, Pelaporan Data Masyarakat Berpenghasilan Rendah - Nanda Devi Permatasari; Masroro Lilik Ekowanti (Public Administration Dept, Faculty of Social and Political Science, 2022)
Surabaya is the second largest city in Indonesia with very fast population growth. Currently, 30 percent of the people in Surabaya are low-income people. In the context of accelerating poverty alleviation, the Surabaya City Government stipulates Surabaya Mayor Regulation Number 58 of 2019, concerning procedures for collecting, processing, utilizing, and reporting data for low-income communities. The theory used is policy implementation according to George Edward III. The factors consist of communication, resources, disposition, and the structure of the bureaucracy. This research is qualitative research with a descriptive approach. The results of this study are limited to the process of collecting and processing MBR data that were found not to be right on target for underprivileged communities in Surabaya. There are obstacles in its implementation, namely in the process of clarity of information and also staff in data collection for MBR. With recommendations 1) The government should often evaluate MBR data every month so that it knows if there are residents whose economic status has improved, 2) Provide clear information to the public, 3) Increase the number of staff for surveys to MBR locations and must have integrity in order to be able to dispel data on residents who are not categorized as MBR.